PROSPECTS FOR LEARNING FOREIGN LANGUAGES THROUGH MODERN TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article analyzes the prospects for learning foreign languages through modern technologies and artificial intelligence. With the development of artificial intelligence and technologies, new opportunities are emerging in the language learning process. The article compares traditional language learning methods with those facilitated by modern technologies, and also examines the role and significance of artificial intelligence in language acquisition.